Potensi Maggot (Black Soldier Fly) sebagai Pakan Ternak di Desa Miri Kecamatan Kismantoro Wonogiri - Sholahuddin Sholahuddin; Ato Sulistyo; Retno Wijayanti; Supriyadi Supriyadi; Subagiya Subagiya (PRIMA: Journal of Community Empowering and Services, 2021)
Potential of Maggot (Black Soldier Fly) as Animal Feed in Miri Village Kismantoro Wonogiri. Cultivation of chicken and catfish was a field of business that was mostly carried out by residents of Miri Village, Kismantoro District, Wonogiri Regency. The high component of feed costs results in low profits. So far, farmers still rely on pellets as the main feed for their livestock. Alternative feeds in the form of Black Soldier Fly (BSF) larvae or maggot were well known to residents, but only a few residents had ever used maggot as feed. Residents had never received education and training on maggot cultivation. This activity aims to increase the knowledge and skills of Miri Village residents in maggot cultivation, the dependence of farmers on artificial feed can be reduced and replaced with feed from maggot cultivation. Activities carried out in the service consist of socialization and training on maggot cultivation. The socialization was in the form of exposure to the benefits and propagation of maggots, while the training materials were the practice of catching eggs, maintaining maggots, and harvesting maggots. The results of the activity showed an increase in participants' knowledge regarding maggot cultivation by 21.32%. The participants also showed interest in carrying out practical activities. The benefits of BSF cultivation include reducing household waste, producing maggots as animal feed, and producing organic fertilizer.